Faster-Than-Nyquist Signal Design for Multiuser Multicell Indoor Visible Light Communications - Yi-Jun Zhu; Wen-Ya Wang; Gang Xin (IEEE Photonics Journal, 2016)
We consider a typical indoor environment, where multiple light-emitting diode (LED) lamps are equipped, and each LED lamp is the base station of an optical cell. A faster-than-Nyquist signal design is presented for multiuser multicell (FTNMM) visible light communication (VLC) broadcasting systems, where all the transmitters transmit independently with a properly designed time delay to achieve multiple times spectral efficiency. The performance of FTNMM is analyzed in view of the minimum Euclidean distance of symbol sequence, and it is proved that the minimum Euclidean distance remains unchanged as transmitter number and symbol length increase. To reduce the complexity of the maximum-likelihood sequence estimation decoding algorithm, a convolutional code structure with dynamic weights and a fast iterative receiver for FTNMM are developed. Simulation results show that the proposed FTNMM obtains significant performance gains over currently available schemes.